PERANCANGAN SISTEM INFORMASI DESA SIBANDANG BERBASIS WEB - Siregar, Lasmita; Simamora, Roni J.; Purba, Eviyanti Novita (Universitas Methodist Indonesia, 2023)
The current development of the village government is good with the existence of a village fund budget from the central government which aims to advance the village, current village development is inseparable from the support of information technology, almost every village needs information technology to improve services to the community. One example is the existence of the internet into the village program, the internet is currently not only enjoyed by urban communities but has reached rural communities. In this era of increasingly advanced technology, a website-based information system can be implemented in Sibandang Village to overcome the above constraints. With the various kinds of information presented. Likewise, village leaders can directly provide or update information related to the villages they are fostering. All forms of information regarding all types of population management can be accessed on the village information system page. The methods used in this study are problem formulation, data collection, problem identification, system development and research methods.